Asuhan Keperawatan Pada Ny. K Keluarga Tn. S Dengan Gangguan Sistem Kardiovaskular : Hipertensi Di Desa Purwodadi RT 03 RW 02 Kecamatan Tonjong Kabupaten Brebes - Rizqi Maulidia; Siti Fatimah; Sujono (STIKES Columbia Asia Medan, 2025)
Hypertension is one of the most prevalent non-communicable diseases and a major contributor to cardiovascular complications among the elderly. This study aimed to provide a comprehensive nursing care intervention for Mrs. K, a hypertensive patient living with her family in Purwodadi Village, Tonjong District, Brebes Regency. The method employed was a case study with a family-centered nursing approach involving assessment, diagnosis, planning, implementation, and evaluation. Data were collected through interviews, observation, documentation, and literature review. The results showed improvements in the patient's blood pressure, increased knowledge and awareness in the family, and positive changes in health-related behaviors. These findings suggest that family-based nursing interventions can significantly enhance hypertension management outcomes. The study implies that nurses should integrate family involvement as a critical component in the care of chronic illness to promote sustainable health improvements.